"Drunk and Proud", from the streets to the stands: America Football Club fans, aguante and alcohol consumption in Mexican football fandom. (June 2014) - Varela, Sergio
An ethnographic description of a typical match day of Ritual del Kaos barra fans provides elements to discuss the consumption of alcohol as a specific practice of aguante . For the young Mexican-organized supporters of professional football clubs the concept of aguante has become the key concept for their daily practices. America Football Club fans of Ritual del Kaos display aguante practices under different denominations. Three of them are descontrol, colorido and carnaval . These concepts are in some sense contradictory one to the other but at the same they are complementary. Descontrol is practiced as if was completely "irrational" and purely emotional. Colorido and carnaval are apparently pure organized and rationalized practices. Nevertheless, the three of them are a combination of emotional and rationalized actions. In that sense, the interpretation of this phenomenon will be given by the melodramatic imagination coordinates.